"Hold This for Me": Counter Memory and Trauma in Dionne Brand's At the Full and Change of the Moon. Issue 2 (2nd April 2020) - Green, Kim
ABSTRACT: African Caribbean Canadian author Dionne Brand's At the Full and Change of the Moon augments many African diasporic narratives' efforts to counter and rewrite exclusive histories. While Brand's novel challenges and nuances dominant historical narratives by offering counter memory of African diasporic experiences, particularly experiences of enslavement, it also simultaneously illuminates the conflicts that emerge when "holding" and passing on memories that are traumatic. Therefore, Brand's text emphasizes both the importance of employing counter memory to revise hegemonic historical narratives and the necessity of assessing the impact of trauma on individual and collective remembrances.